Hydrogen Sulfide From Cysteine Desulfurase, Not 3-Mercaptopyruvate Sulfurtransferase, Contributes to Sustaining Cell Growth and Bioenergetics in E. coli Under Anaerobic Conditions - Wang, Jun; Guo, Xin; Li, Heng; Qi, Haizhen; Qian, Jing; Yan, Shasha; Shi, Junling; Niu, Weining (Frontiers in Microbiology, 2019)
Endogenous hydrogen sulfide (H2S), which is primarily generated by 3-mercaptopyruvate sulfurtransferase (3-MST) in Escherichia coli(E. coli) under aerobic conditions, renders bacteria highly resistant to oxidative stress. However, the biosynthetic pathway and physiological role of this gas under anaerobic conditions remains largely unknown. In the present study, we demonstrate that cysteine desulfurase (IscS), not 3-MST, is the primary source of endogenous H2S in E. coli under anaerobic conditions. A significant decrease in H2S production under anaerobic conditions was observed in E. coli upon deletion of IscS, but not in 3-MST-deficient bacteria (ΔmstA).Furthermore, the H2S-producing activity of recombinant IscS using L-cysteine as a substrate exhibited an approximately 2.6-fold increase in the presence of dithiothreitol (DTT), indicating that H2S production catalyzed by IscS was greatly increased under reducing conditions. The activity of IscS was regulatedunder the different redox conditions and the midpoint redox potential was determined to be -329 ± 1.6 mV.Moreover, in E.coli cells H2S production from IscS is regulated under oxidative and reductive stress.A mutant E. coli (ΔiscS) strain lacking a chromosomal copy of the IscS-encoding gene iscSshowed significant growth defects and low levels of ATP under both aerobic and anaerobic conditions. The growth defects could be fully restored after addition of 500 μM Na2S (an H2S donor) under anaerobic conditions, but not by the addition of cysteine, sodium sulfite or sodium sulfate. We also showed that the addition of 500 μM Na2Sto culture medium stimulates ATP synthesis in the mutant E. coli (ΔiscS) strainin the logarithmic growth phase but suppresses ATP synthesis in wild-type E. coli. Our results reveal a new H2S-producing pathway in E. coli under anaerobic conditions and show that hydrogen sulfide from IscS contributes to sustaining cell growth and bioenergetics under oxygen-deficient conditions.